Successful Management of a Recurrent Supralevator Abscess: A Case Report. (7th May 2012) - Sanyal, S.; Khan, F.; Ramachandra, Prashanth
Abstract : Anorectal abscesses are commonly encountered in clinical surgical practice. These abscesses require surgical management. Supralevator abscesses are thought to originate either from an ischiorectal or intersphincteric abscess extension or from an intraperitoneal source. These abscesses are quite uncommon and present a difficult surgical problem. We present a case here of a 42-year-old female with a recurrent supralevator abscess requiring multiple surgical procedures for adequate drainage and care of her abscess.